Identification of movement coordination deficiencies in Singapore primary school children - Toh, Jun Hong (2016)
PURPOSE This study aimed to identify children with movement coordination deficiencies to understand the current prevalence of such deficiencies in Singapore children. A severe form of this deficiency is known as Developmental Coordination Disorder (DCD). Movement assessment tools provide a less costly and more convenient method, compared to official diagnoses, in understanding children’s movement coordination abilities. METHODS 26 Primary 2 children, 13 males and 13 females, aged 7-8 from a Singapore school were recruited for this study. They underwent an object control skills assessment via the Test of Gross Motor Development 2nd Edition (TGMD-2). The skills were assessed by 2 qualified assessors, who underwent inter- and intra-rater reliability testing before the assessment. A checklist with the 3 main developmental stages for each skill, namely Initial, Transition, and Mature, was used with the TGMD-2’s skill criteria placed under the Mature stage. Participants also completed a form giving information on height, weight, family background and level of physical activity (PA) outside school. RESULTS 16 participants (6 male, 10 female) fell in the <1 percentile. There was a correlation between PA participation outside school and skill performance, but not between BMI and skill performance. CONCLUSION The high prevalence of Singapore primary school children with movement coordination deficiencies, or at risk of DCD, is of concern especially to parents and teachers. Future studies could include larger sample sizes, and/or participants from different age groups, to determine whether the results can be generalised to the Singapore population and whether intervention would be necessary.